1988
DOI: 10.1111/j.1574-6968.1988.tb03147.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of penicillin on the synthesis of membrane proteins of Chlamydia trachomatis LGV2 serotype

Abstract: Cultures of LLC‐MK2 cells were infected with Chlamydia trachomatis LGV2 serotype and incubated in medium containing 200 units per ml of penicillin. Forty‐eight hours after infection, cells were removed and chlamydiae purified. By Coomassie blue‐stained polyacrylamide gels, penicillin‐treated chlamydiae showed to be deficient in 60 K and 62 K outer membrane proteins. By using a more sensitive immunoblotting technique, in conjunction with human and animal immune sera containing antibodies specific for the 60 K a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…It has been reported that b-lactam antibiotic treatments cause repression of omcB gene expression (omcB encodes the cysteine rich 60 kDa outer-membrane protein) (Cevenini et al, 1988;Sardinia et al, 1988). To verify that penicillin treatment in our system was consistent with these observations, we followed the accumulation of the OmcB protein by ELISA using polyclonal antisera raised against C. trachomatis OmcB (Watson et al, 1994).…”
Section: Effect Of Penicillin On Bgmk Cells Infected With C Trachomatissupporting
confidence: 58%
“…It has been reported that b-lactam antibiotic treatments cause repression of omcB gene expression (omcB encodes the cysteine rich 60 kDa outer-membrane protein) (Cevenini et al, 1988;Sardinia et al, 1988). To verify that penicillin treatment in our system was consistent with these observations, we followed the accumulation of the OmcB protein by ELISA using polyclonal antisera raised against C. trachomatis OmcB (Watson et al, 1994).…”
Section: Effect Of Penicillin On Bgmk Cells Infected With C Trachomatissupporting
confidence: 58%
“…A well-known example is the 60-kDa cysteine-rich protein (CRP), which is abundant in EB envelopes. The 60-kDa CRP was either markedly diminished or completely absent in early studies of C. trachomatis strains exposed to ␤-lactam antibiotics (23,104), IFN-␥ (7, 10), or heat shock (53). Another study reported the absence of the Hc-1 and Hc-2 DNA-binding proteins (involved in chromosomal condensation) in IFN-␥-exposed C. trachomatis, although interestingly, the 60-kDa CRP was not down-regulated (52) ( Table 2).…”
Section: Cpafmentioning
confidence: 99%
“…Penicillin inhibits RB division and RB to EB differentiation, but has no known effect on RB metabolism (37,38). As shown in Fig.…”
Section: Bacterial Protein Synthesis Is Required For the Induction Ofmentioning
confidence: 99%